Perceived organizational support as key success factor to improve employee performance besides organization commitment and organizational citizenship behavior - Ridwan, Muhammad; Puspa , Tiara (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2022)
This research aims to investigate and demonstrate the impact of perceived organizational support and organizational commitment on organizational citizenship behavior and the performance of university lecturers. The object of research is a lecturer who serves at a private university located in West Sumatra. The effects and implications that were analyzed and proven in this study were carried out partly or jointly. The descriptive and verification approach was employed with a sample of 320 respondents, and the data analysis method was the SEM (Structural Equation Modeling) method utilizing the Lisrel Program. According to the study's findings, perceived organizational support and organizational commitment have a positive and significant effect on organizational citizenship behavior. It was discovered that perceived organizational support, organizational commitment, and organizational citizenship behavior have a positive and significant impact on lecturer performance. This study concluded and indicated that it is required to incorporate perceived organizational support that benefits employees, organizational commitment, and organizational citizenship behavior to increase employee performance. Further research suggested the influence and impact of other variables not only from the individual perception but also from the level of team and organization.